2018
DOI: 10.12688/f1000research.13016.2
|View full text |Cite
|
Sign up to set email alerts
|

The rise and fall of machine learning methods in biomedical research

Abstract: In the era of explosion in biological data, machine learning techniques are becoming more popular in life sciences, including biology and medicine. This research note examines the rise and fall of the most commonly used machine learning techniques in life sciences over the past three decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 10 publications
(10 reference statements)
1
7
0
Order By: Relevance
“…In the last decade, there has been increased use knowledge discovery techniques of artificial intelligence in pharmacoepidemiology. This result is in line with those of Koohy (2017) who showed an increased popularity of machine learning methods for biomedical research from 1990 to 2017. We strongly believe that one of the major consequences for the increased interest in applying machine learning techniques over the years is the dramatic growth in size and complexity of clinical and biological data that have led to the necessity of combining mathematics, statistics, and computer science to extract actionable insight.…”
Section: Discussionsupporting
confidence: 91%
“…In the last decade, there has been increased use knowledge discovery techniques of artificial intelligence in pharmacoepidemiology. This result is in line with those of Koohy (2017) who showed an increased popularity of machine learning methods for biomedical research from 1990 to 2017. We strongly believe that one of the major consequences for the increased interest in applying machine learning techniques over the years is the dramatic growth in size and complexity of clinical and biological data that have led to the necessity of combining mathematics, statistics, and computer science to extract actionable insight.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, they found that SVMs significantly outperformed random forests, although random forests outperformed SVMs in some cases[ 42 ]. Perhaps in part due to these highly cited studies, SVMs and random forests have been used heavily in diverse types of biomedical research over the past two decades[ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Modern health care can take advantage of the potential that AI offers, and research has been growing across medical disciplines. From 2001 to 2017, ML biomedical publications grew 6% per year 20 . A PubMed/MEDLINE search of [“Machine Learning” AND “Spine”] yielded 153 original research articles on the application of ML to spine surgery alone (Fig.…”
Section: What Is Ml?mentioning
confidence: 99%